Treatment with coenzyme Q10, omega-3-polyunsaturated fatty acids and their combination improved bioenergetics and levels of coenzyme Q9 and Q10 in skeletal muscle mitochondria in experimental model of arthritis - Kucharská, J; Poništ, S; Vančová, O; Gvozdjáková, A; Uličná, O; Slovák, L; Taghdisiesfejir, M; Bauerová, K (Physiological research, 2021)
Rheumatoid arthritis (RA) and its animal model adjuvant arthritis (AA) are inflammatory diseases characterized by chronic inflammation, systemic oxidative stress and disturbed mitochondrial bioenergetics of skeletal muscle. The present study aimed to evaluate the effects of coenzyme Q10 - CoQ10 (100 mg/kg b.w.), omega-3-polyunsaturated fatty acids - omega-3-PUFA (400 mg/kg b.w.) and their combined treatment in AA on impaired skeletal muscle mitochondrial bioenergetics, inflammation and changes in levels CoQ9 and CoQ10 in plasma. Markers of inflammation (C-reactive protein, monocyte-chemotactic protein-1), antioxidant capacity of plasma, respiratory chain parameters of skeletal muscle mitochondria and concentrations of CoQ9 and CoQ10 in plasma and in muscle tissue were estimated. Treatment of the arthritic rats with CoQ10, omega-3-PUFA alone and in combination partially reduced markers of inflammation and increased antioxidant capacity of plasma, significantly increased concentrations of coenzyme Q in mitochondria and improved mitochondrial function in the skeletal muscle. Combined treatment has similar effect on the mitochondrial function as monotherapies; however, it has affected inflammation and antioxidant status more intensively than monotherapies. Long-term supplementary administration of coenzyme Q10 and omega-3-PUFA and especially their combination is able to restore the impaired mitochondrial bioenergetics and antioxidant status in AA.
Keywords: C-reaktivní protein; Arthritis, Rheumatoid; Rats, Inbred Lew; krysa rodu Rattus; Antioxidants; zvířata; omega-3 mastné kyseliny; Fatty Acids, Omega-3; chemokin CCL2; revmatoidní artritida; antioxidancia; artritida experimentální; Male; Chemokine CCL2; potravní doplňky; Dietary Supplements; Ubiquinone; potkani inbrední LEW; Rats; Animals; Mitochondria, Muscle; mužské pohlaví; C-Reactive Protein; svalové mitochondrie; ubichinon; Arthritis, Experimental